Influencia de la metodológica docente en la área de lengua y literatura para el desarrollo de la lectura comprensiva en los estudiantes de sexto y sèptimo año de educaciòn basica en la Escuela General Alcides Pesantes Villacis en el periodo 2013-2014 - Jaèn Salazar, Alexandra del rocìo (2014)
The present investigation has allowed an analysis of the impact of the teaching methodology in the development of reading comprehension of students. On the theoretical basis of this research we determined that understand a text is to find meaning, to relate it to what you already know and what interests. Given the results of field research we have determined that teachers do not apply methodological strategies to develop reading comprehension, that are not achieving high levels of skill development in reading performance criterion.In the development of this work it was raised as a central objective: To determine the influence of the teaching methodology in the area of language and literature in the development of reading comprehension in the sixth and seventh year of basic education of the General School. Alcides Pesantes. The field work consisted of conducting surveys for teachers and students and teachers courtly observations. From the results of this investigation conclusions, recommendations were made and concludes with the proposed intervention